Symbolika światła w narracji synoptyków o przemienieniu Jezusa - Janczak, Galina (Verbum Vitae, 2016)
The article deals with the metaphor of light as used in the three synoptic passages recounting the Transfiguration of Jesus. Light was visible to the disciples, thus the Transfiguration had an external character, expressed in the dazzling white clothing of Jesus and the radiance of his face as the sun. The synoptic Gospels’ symbolism of light is based on OT traditions such as the Mosaic theophany on Sinai and the apocalyptic vision of the Son of Man in Dn 7. By the term light (and semantically related words) the Gospel writers attempt to describe the transcendent reality which is manifested to selected disciples. The shining radiance of the transfigured Jesus, as well as the dazzling white garment, both serve to reveal Him as a heavenly figure. The symbolism of light as used in this pericope projected a divine attribute, a meaning fully comprehensible within the Jewish and Greek worlds: The bright radiance of the transfigured Jesus is an unmistakable element of His glory.